Multisensory presence in virtual reality: Possibilities and limitations - Gallace, A; Ngo, M; Sulaitis, J; Spence, C (IGI Global, 2011)
Perception in the real world is inherently multisensory, often involving visual, auditory, tactile, olfactory, gustatory, and, on occasion, nociceptive (i.e., painful) stimulation. In fact, the vast majority of life's most enjoyable experiences involve the stimulation of several senses simultaneously. Outside of the entertainment industry, however, the majority of virtual reality (VR) applications thus far have involved the stimulation of only one, or at most two, senses, typically vision, audition, and, on occasion, touch/haptics. That said, the research that has been conducted to date has convincingly shown that increasing the number of senses stimulated in a VR simulator can dramatically enhance a user's 'sense of presence', their enjoyment, and even their memory for the encounter/experience. What is more, given that the technology has been improving rapidly, and the costs associated with VR systems are continuing to come down, it seems increasingly likely that truly multisensory VR should be with us soon (albeit 50 years after Heilig, 1962, originally introduced Sensorama). However, it is important to note that there are both theoretical and practical limitations to the stimulation of certain senses in VR. In this chapter, after having defined the concept of 'neurally-inspired VR', we highlight some of the most exciting potential applications associated with engaging more of a user's senses while in a simulated environment. We then review the key technical challenges associated with stimulating multiple senses in a VR setting. We focus on the particular problems associated with the stimulation of the senses of touch, smell, and taste. We also highlight the problems associated with the limited bandwidth of human sensory perception and the psychological costs associated with users having to divide their attention between multiple sensory modalities simultaneously. Finally, we discuss how the findings provided by the extant research in the cognitive neurosciences might help to overcome, at least in part, some of the cognitive and technological limitations affecting the development of multisensory VR systems. © 2012, IGI Global.